Perbandingan Hasil Terjemahan Translator Xp Enterprise, Google, dan Alfa Link Seri Eic 1250cl – Super 1 - Wayan Pageyasa (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Currently, the translation was more important. Therefore, efforts were made to facilitate translation. One way is by creating a machine translator. However, the accuracy of the machines still need to be tested. Acceptance of machine translation results should be viewed carefully. This small study in a simple view of the translation level of the text. The conclusion is that the translator machine translation results are relatively understandable. In other words, the machine translator can be relied upon to translate texts of a general nature and using colloquialisms such as a website content and guidelines. But for scientific manuscripts in language that is not unusual and not the everyday language, the machine can not be relied upon to translate. Nevertheless, the machine translator is very helpful especially if we find that no foreign content in English, like Spanish, Chinese, German, and others. In general, machine translation can help us understand the purpose of the foreign content with the translation of "rough".